Attachment Theory and Maternal Drug Addiction: The Contribution to Parenting Interventions - Parolin, Micol; Simonelli, Alessandra (Frontiers in Psychiatry, 2016)
Children’s emotional and relational development can be negatively influenced by maternal substance abuse, particularly through a dysfunctional caregiving environment. Attachment Theory offers a privileged framework to analyze how drug addiction can affect the quality of adult attachment style, parenting attitudes and behaviors toward the child, and how it can have a detrimental effect on the co-construction of the attachment bond by the mother and the infant. Several studies, as a matter of fact, have identified a prevalence of insecure patterns among drug-abusing mothers and their children. Many interventions for mothers with Substance Use Disorders have focused on enhancing parental skills, but they have often overlooked the emotional and relational features of the mother–infant bond. Instead, in recent years, a number of protocols have been developed in order to strengthen the relationship between drug-abusing mothers and their children, drawing lessons from Attachment Theory. The present study reviews the literature on the adult and infant attachment style in the context of drug addiction, describing currently available treatment programs that address parenting and specifically focus on the mother–infant bond, relying on Attachment Theory.